Economics of Tobacco Toolkit, Tool 3 : Economic Analysis of Tobacco Demand - Wilkins, Nick (World Bank, Washington, DC, 2013)
The tobacco epidemic is a worldwide phenomenon with significantly destructive effects on developing, transitional, and industrialized nations. The first scientific evidence on the health consequences of tobacco consumption-specifically, smoking-was discovered in industrialized nations. As a result, the economic analysis of tobacco control issues began and was developed in these countries. This tool attempts to explain the process of analysis of demand for tobacco products as simply as possible. It includes discussions of basic economic and analysis principles (written for non-specialists such as policy makers and analysts) and more advanced technical points (intended for use by the economists and econometricians who will undertake the actual demand analysis). Consumption of tobacco products includes both smoked categories (e.g., cigarettes, hand-rolled tobacco, pipe tobacco, cigars, bidis, kreteks, etc.) and smokeless types (such as snuff and chewing tobacco). In industrialized countries, cigarettes disproportionately influence tobacco epidemics. This tool discusses and presents, in technical detail, each of the steps necessary to conduct an economic demand analysis on tobacco products. In addition, the reader is presented the fundamentals of demand analysis, including its purpose, assumptions, and requirements. In turn, the reasons to intervene in the market for tobacco products stem from the destructive nature of tobacco consumption. Smoking is the single largest preventable cause of premature death in industrialized countries. In economic terms, the principle of consumer sovereignty holds that individuals know what products are in their best interests to consume. Provided consumers know the risks concerned and internalize all the costs and benefits involved, private consumption decisions result in the most efficient allocation of society's scarce resources. Tobacco products are available to consumers for a price, and an issue of great interest to tobacco control advocates (and the tobacco industry) is to what extent are consumers willing to buy those tobacco products. For instance, the willingness to buy is strongly influenced by such characteristics as the consumer's sense of value, income level, and taste.